Dose dependent effect of ginseng on high fat diet induced hyperlipidemia in rats: A preventive clue for coronary artery diseases in experimental rats. - Rehan, Rabia; Mubeen, Sahar; Imtiaz, Fauzia; Kamran, Mahrukh; Mohammad Sarfaraz (International Journal of Endorsing Health Science Research, 2021)
Background: Coronary artery diseases are among the most challenging diseases in this era. Improper dietary habits and sedentary lifestyles are considered as foundation stones for metabolic disorders, including hyperlipidemia, the leading cause of coronary artery diseases and hypertension. This experiment was designed to study the dose-dependent effect of ginseng on high fat diet induced hyperlipidemia in animal models. Methodology: This experimental study was conducted at Dow University of Health Sciences, including 50 male Albino Wistar rats. The rats were randomly divided into 5 groups of 10 animals each. Group 1 was on a normal balanced diet; group 2 was on a high fat diet (HFD), group 3 was on HFD plus ginsenoside 100 mg/kg body wt, group 4 was on HFD plus ginsenoside 200 mg/kg body wt, group 5 was on HFD plus ginsenoside 400 mg/kg body wt. Animals were sacrificed after 12 weeks; blood was drawn then sent to DDRRL for lipid profile. Results: The results revealed that HFD increases body fats, weight increases from initial weight to 27.53% in obese control group 2 while after treating with ginsenoside weight reduced to 11.6%. Lipids levels in the blood; in the obese control group, mean triglyceride level increases from 45 mg/dl to 128.50 mg/dl, mean cholesterol level from 56.3 mg/dl to 106.2 mg/dl and low-density lipoprotein (LDL) is increased from 6 to 11.9 mg/dl. While concurrent administration of ginseng root extract (ginsenoside) reduces the Lipid levels in blood according to the dosage of ginseng root extract, the mean triglyceride level in group 4 is reduced to 46.10 mg/dl from 128.50 mg/dl. The mean cholesterol level in group 4 is reduced to 400 mg/dl from 106.2 mg/dl. LDL is reduced in group 4 to 7.5 mg/dl from 11.9 mg/dl. Conclusion: This study provides evidence that Ginsenoside has an anti-hyperlipidemic effect, so it might be helpful in preventing coronary artery disease.